2004
DOI: 10.1074/jbc.m312625200
|View full text |Cite
|
Sign up to set email alerts
|

S-Adenosylmethionine Decarboxylase Degradation by the 26 S Proteasome Is Accelerated by Substrate-mediated Transamination

Abstract: The short-lived enzyme S-adenosylmethionine decarboxylase uses a covalently bound pyruvoyl cofactor to catalyze the formation of decarboxylated S-adenosylmethionine, which then donates an aminopropyl group for polyamine biosynthesis. Here we demonstrate that S-adenosylmethionine decarboxylase is ubiquitinated and degraded by the 26 S proteasome in vivo, a process that is accelerated by inactivation of S-adenosylmethionine decarboxylase by substrate-mediated transamination of its pyruvoyl cofactor. Proteasome i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 51 publications
(48 reference statements)
3
22
0
Order By: Relevance
“…Total protein from the whole inoculated plants was used for immunoblot with anti-myc antibody (top) and Ponceau S staining (bottom) of ribulose-1,5-bisphosphate carboxylase/ oxygenase (Rubisco) protein is shown as a loading control. Persson, 1993;Berntsson et al, 1999;Yerlikaya and Stanley, 2004). Our results of the wheat germ and Arabidopsis cell-free assays also indicated that Arabidopsis SAMDC1 is degraded in a similar 26S proteasome-dependent manner.…”
Section: Bsctv C2 Positively Regulates Samdc1supporting
confidence: 59%
See 2 more Smart Citations
“…Total protein from the whole inoculated plants was used for immunoblot with anti-myc antibody (top) and Ponceau S staining (bottom) of ribulose-1,5-bisphosphate carboxylase/ oxygenase (Rubisco) protein is shown as a loading control. Persson, 1993;Berntsson et al, 1999;Yerlikaya and Stanley, 2004). Our results of the wheat germ and Arabidopsis cell-free assays also indicated that Arabidopsis SAMDC1 is degraded in a similar 26S proteasome-dependent manner.…”
Section: Bsctv C2 Positively Regulates Samdc1supporting
confidence: 59%
“…The PEST sequence has been reported to be located in some proteins with fast turnover rates and be essential for the interaction between SCF complex and target proteins, which consequently leads to ubiquitination/26S proteasome-mediated degradation (Kiernan et al, 2001;Berset et al, 2002;Blondel et al, 2005;Pal et al, 2007). Human SAMDC was reported to have a short half-life and is regulated at multiple levels, such as the transcriptional, translational, and posttranslational levels (Shantz et al, 1992;Stanley et al, 1994;Hanfrey et al, 2003;Yerlikaya and Stanley, 2004). Taking all the information above together, we wanted to ask whether the interaction with BSCTV C2 can affect with the stability of SAMDC1.…”
Section: Bsctv C2 Interacts With Arabidopsis Samdc1mentioning
confidence: 99%
See 1 more Smart Citation
“…AdoMetDC turnover accelerates when concentrations of Spd and Spm are high [67]. Degradation of AdoMetDC by polyubiquitination via the proteasome is accelerated when its pyruvoyl group is transaminated and transformed into alanine by its substrate AdoMet [74]. This transformation is suggested to induce a conformational change in this enzyme, making its ubiquitination site more accessible and thus more prone for degradation [61,74].…”
Section: Polyamines and S-adenosylmethionine Decarboxylase (Adometdc)mentioning
confidence: 90%
“…The ODC antizyme encoded by Oaz, as well as ribosomal proteins L34 and S20, inhibit ODC and arginine decarboxylases (Panagiotidis et al 1995). The ODC and SAMDC are degraded by the 26S proteasome (Yerlikaya & Stanley 2004) which is encoded by Psmc3 and Psmc5. The ODC antizyme also inhibits polyamine uptake and stimulates excretion (Sakata et al 2000).…”
Section: Calcium Ion Muscle Contraction and Cell Proliferationmentioning
confidence: 99%